Naujosios žiniasklaidos vaidmuo sudarant darbotvarkę Baltarusijoje - Martinovich, Victor (Information & Media, 2012)
The role of the new media in agenda setting in BelarusVictor MartinovichSummaryThe author starts with defining the nature of the political regime that acts in Belarus, providing a list of the key features that are important for media behaviour. The list is extracted from the relevant comparative researches focused on Belarus. After describing the regime as a set of rules for the media, the text then proceeds to the specific morphology of the Belarussian new media that do not comply with the basic characteristics proposed by media researchers and thus can be recognized as old media restructured to meet the ethics and principles of the Internet. Then the author deals with the agenda setting process in Belarus and proposes his own interpretation of the classical logistics of this process in specific Belarussian circumstances where the list of power-bearing actors is dramatically reduced. The paper is finalized with showing the new possibilities that the media as an actor of public policy have obtained in the agenda setting after appearance of Web 2.0 when sites the have been re-structured on the basis of the user-generated content which helps to retrieve the media’s autonomy and possibilities to influence the agenda setting.Key words: public policy theory, new media, agenda-setting process, political regimes